Elements of Peruvian necropolitics: the death of Abimael Guzmán and the discarding of ‘terrorist’ remains - Valérie Robin Azevedo (Human Remains and Violence)
In Peru, in September 2021, the death in prison of Abimael Guzmán, founder of the PCP-Sendero Luminoso and the issue of the ‘terrorist’s’ funeral represented the climax of media and political indignation. The State therefore proceeded to dispose of the unwelcome remains, revealing that funeral rites for subversives and public mourning for their families are hardly conceivable here. This article shows how the denial of funerals and burials has been legitimised by a complex process of exclusion, dehumanisation and even discarding of the deceased’s body. It examines the trajectory of Guzmán’s mortal remains to shed light on the necropolitical dimension of the Peruvian State’s actions. In a country supposed to be a post conflict one, the implementation of a public policy of dignified burial coexists with the deprivation of funerals and even of a grave for some of the former actors of the internal armed conflict, various logics of disqualification playing a key role in these practices of funerary segregation.